2020
DOI: 10.3892/ol.2020.12407
|View full text |Cite
|
Sign up to set email alerts
|

Benzidine promotes the stemness of bladder cancer stem cells via activation of the Sonic hedgehog pathway

Abstract: Substantial evidence suggests that cancer stem cells (CSCs) are the main cause of the initiation, progression and recurrence of tumors. Benzidine has been identified as a risk factor for bladder cancer. The aim of the present study was to investigate the effects of benzidine on bladder CSCs (BCSCs) and the possible mechanism underlying its action. The bladder cancer cell lines UM-UC-3 and EJ were maintained in serum-free medium and cells forming three-dimensional spheres were characterized as BCSCs. The sphere… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
6
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
3
1
1

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(7 citation statements)
references
References 34 publications
(32 reference statements)
0
6
0
Order By: Relevance
“…Substantial epidemiological researches concerning the association between benzidine and BC have been completed since 1950s [15]. In vitro and in vivo researches have assessed the genetic expression variations related to acute benzidine exposure [12,[16][17][18][19][20][21][22]. Previously, we reported that benzidine treatment could result in increased cellular proliferation, EMT alteration and MAPK activation in SV-HUC-1 and T24 cells [12,[17][18][19][20][21].…”
Section: Discussionmentioning
confidence: 99%
See 4 more Smart Citations
“…Substantial epidemiological researches concerning the association between benzidine and BC have been completed since 1950s [15]. In vitro and in vivo researches have assessed the genetic expression variations related to acute benzidine exposure [12,[16][17][18][19][20][21][22]. Previously, we reported that benzidine treatment could result in increased cellular proliferation, EMT alteration and MAPK activation in SV-HUC-1 and T24 cells [12,[17][18][19][20][21].…”
Section: Discussionmentioning
confidence: 99%
“…Previously, we reported that benzidine treatment could result in increased cellular proliferation, EMT alteration and MAPK activation in SV-HUC-1 and T24 cells [12,[17][18][19][20][21]. In addition, the enhancement of the stemness of BC stem cells was discovered after benzidine treatment [22]. Nonetheless, the causal links by which benzidine induced the developmental process of BC are still elusive.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations